PENILAIAN SENSORIS DAGING DAN BAKSO DARI EMPAT GALUR AYAM BURAS YANG DIBERI JAMU FERMENTASI - Isye Jean Liur; Astri Dwiyanti Tagueha (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2019)
The objective of this research was to known sensory quality of meat (carcass) and bakso from four strain of native chicken whose receive fermented herbs. This study used four treatments (G1 – Native, G2 – Bangkok, G3 – KUB, G4 – Bangkok Hybrid) and three replications, each of them was observed by 20 panelists. During three months of observation, each treatment received same dosage and frequency of fermented herbs and also the number of commercial feed. The results showed that : (1) the sensory quality of meat (carcass) revealed the differences in colour and acceptability but not in flavor and texture, and (2) the sensory quality of bakso revealed the differences only in colour, yet its absent in flavor, texture, and tenderness.